2016
DOI: 10.5099/aj160200123
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Heterogeneity of Natural Cordyceps sinensis with Multiple Ophiocordyceps sinensis Fungi Challenges the Anamorph-Teleomorph Connection Hypotheses

Abstract: Natural Cordyceps sinensis is a traditional Chinese medicine with a long history of use as a folk medicine in China. However, whether Ophiocordyceps sinensis is a single fungus or a collective name for multiple fungi remains controversial, as does the anamorph-teleomorph connection of O. sinensis. Although Hirsutella sinensis has been widely considered the sole anamorph of O. sinensis, direct evidence supporting this hypothesis is lacking. This paper reviews the molecular heterogeneity findings of C. sinensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(110 citation statements)
references
References 46 publications
3
107
0
Order By: Relevance
“…Among these methodologies, RAPD molecular marker polymorphism analysis is the most frequently used technique for comparing overall similarities or dissimilarities (genetic distances) and exploring the phylogenetic (cluster) relationship between the test systems [2,29,[32][33][34][35][36][37][38][39][40][41], although it has been suggested that ISSR may be more sensitive than RAPD [42][43][44] and costly metagenomic approaches may demonstrate advantages in qualitative studies of microbial genetic diversity and molecular ecology [45][46][47]. Among the key factors in study design for molecular marker polymorphism comparisons, the importance of unbiased selection of a plurality of random primers for random amplification of the genomic DNA templates isolated from the examined systems has been addressed [1][2][3][4]40,41]. The use of only a few random primers without reporting the objectivity and representativeness of the selection could lead to bias in the data analysis and thus biased conclusions [1][2][3][4]40,41,48].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these methodologies, RAPD molecular marker polymorphism analysis is the most frequently used technique for comparing overall similarities or dissimilarities (genetic distances) and exploring the phylogenetic (cluster) relationship between the test systems [2,29,[32][33][34][35][36][37][38][39][40][41], although it has been suggested that ISSR may be more sensitive than RAPD [42][43][44] and costly metagenomic approaches may demonstrate advantages in qualitative studies of microbial genetic diversity and molecular ecology [45][46][47]. Among the key factors in study design for molecular marker polymorphism comparisons, the importance of unbiased selection of a plurality of random primers for random amplification of the genomic DNA templates isolated from the examined systems has been addressed [1][2][3][4]40,41]. The use of only a few random primers without reporting the objectivity and representativeness of the selection could lead to bias in the data analysis and thus biased conclusions [1][2][3][4]40,41,48].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have reported the molecular heterogeneity of C. sinensis-associated fungi of the genera Hirsutella, Paecilomyces and Tolypocladium as well as Geomyces pannorum, Cladosporium macrocarpum, Phaeosphaeria pontiformis and Neosetophoma samarorum (in total, more than 90 species spanning at least 37 genera) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. SNP mass spec genotyping and amplicon sequencing with or without molecular cloning have identified the mutant ITS sequences of at least 17 genotypes of O. sinensis fungi with multiple, scattered point mutations or DNA segment substitution hereditary variations from the natural C. sinensis insect-fungi complex [1][2][3][4][10][11][12][13]19,[22][23][24][25][26][27][28]. The successful production of artificial C. sinensis enabled the molecular examination of the fungal strains that were used as inoculation agents and the correlation of the genotype results with the finished product, artificial C. sinensis [28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations